Blind recognition of RSC based on logarithmic conformity - Zhaogen ZHONG; Zhaojun WU; Limin ZHANG; Zhiqing WANG (Tongxin xuebao)
A new algorithm based on logarithmic conformity was proposed.Firstly,based on the probability of total RSC coding equation,the concept of logarithmic coincidence degree,which could measure the establishment of coding equation,was introduced.Then because of constraint length of RSC,the polynomial database could be generated,and then logarithmic conformity of every polynomial could be calculated when traversing the database.As the results,the RSC could be recognized,because the correct polynomial could make the conformity maximum.The algorithm has small amount of calculation because of finite traversal,which was only related to amount of intercepted data,besides,this algorithm has good error tolerance by soft decisions.The simulation results show that the correct ratio of recognition can reach 90% at SNR of 0 dB and its performances are obviously superior to those of existing algorithms.